Changes in the hydrophobic-hydrophilic cell surface character of Halomonas elongata in response to NaCl. - Hart, D J (1988)
Phase-partitioning studies of the euryhaline bacterium Halomonas elongata demonstrated that the hydrophobic-hydrophilic nature of the cell surface changed as the bacterium grew in different NaCl concentrations. Mid-log-phase cells grown in a high (3.4 M) NaCl concentration were more hydrophilic than were cells grown in a low (0.05 M) NaCl concentration. Mid-log-phase cells from defined medium containing 3.4 M NaCl normally produced a hydrophobicity reading of only 14 (hexadecane hydrophobicity = 100), while corresponding cells from defined medium containing 0.05M NaCl gave a hydrophobicity reading of 90. Compared with cells grown in low salt concentrations, cells grown in high salt concentrations were more hydrophilic at all stages of growth. Rapid suspension of log-phase cells grown in 1.37 M NaCl into a 0.05 or 3.4 M NaCl solution produced no detectable rapid changes in surface hydrophobicity. These data suggest that as H. elongata adapts to different NaCl concentrations, it alters the affinity of its outermost cell surface to water.